Multi-level analysis of the enamel microstructure in the substantiation of microinvasive technologies of treatment of focal demineralization of enamel in patients of orthodontic profile - O. S. Gileva; A. D. Levitskaya; E. S. Syutkina; I. N. Khalyavina (LLC "Endo Press", 2020)
Relevance. Focal enamel demineralization is one of the significant problems of dentistry, given that the initial stages are manifested by demineralization, rapidly progressing in the absence of timely adequate therapy.Aim. To substantiate the feasibility of using the microinvasive method of treating focal enamel demineralization in orthodontic patients based on multilevel analysis of the enamel microstructure using modern clinical and high-precision experimental studies.Material and methods. Enamel artificial caries was modeled on the vestibular surface of 42 teeth using an original technique, as well as special hardware and instrumentation.Results. When analyzing the SEM data, an inhomogeneous rough enamel microrelief with the presence of numerous depressions, depressions, and characteristic ridges was established. SEM certification of the longitudinal section of the tooth showed that with an increase of 217 times in the section of artificial caries, enamel destruction zones are determined from 200 to 450 μm deep, most often in the shape of a triangle, with the apex facing the enamel-dentine border.Conclusion. The results of a multilevel (macro-, meso- and microscopic) analysis of the structure and micromechanical properties of enamel in the focus of demineralization made it possible to assess the validity of the developed experimental methods for artificial caries of enamel, to obtain voluminous information about the structural and functional disorders developing in it, to justify the expediency of the pathogenetic use of the microinvasive infiltration treatment method.